Knowledge, attitude and perceptions of university students towards educational loans in Malaysia - Abu Bakar, Elistina; Masud, Jariah; Md Jusoh, Zuroni (Springer, 2006)
National Higher Education Fund Corporation (PTPTN) loan is the major source of financing tertiary education in Malaysia. Non-repayment of the loan among university students after they have graduated becomes a major problem to the government since the total amount of loan available to the students is depended on the loan repayment. This study sought to examine the students’ knowledge and attitude regarding the loan. Three aspects of focus are knowledge, attitude and perception of students towards the loan and the repayment of the loan. This study also analyzed the legal literacy of students towards the PTPTN agreement. A total of 1,500 students of University Putra of Malaysia participated in the study and data were collected using self-administered questionnaire. The findings revealed that students have good knowledge about PTPTN loan agreement but there were a significant proportion of students with negative attitudes towards the repayment of the loan. Majority of them perceived the loan as a burden to them and it limits many options of their life after graduation.